A pilot study comparing bioelectrical impedance analysis and body mass index in determining obesity among staff of a Ghanaian University. Issue 2 (11th March 2019) - Hayford, Frank Ekow Atta; Appiah, Collins Afriyie; Al Hassan, Taofik; Asamoah-Boakye, Odeafo; Asante, Matilda
Abstract : Purpose: In Ghana, the body mass index (BMI) is widely used in clinical practice in assessing weight status, but it is limited as a measure of adiposity. The purpose of this study was to compare bioelectrical impedance analysis (BIA) and body mass index (BMI) methods in determining obesity among some Ghanaians. Design/methodology/approach: This was a cross-sectional survey involving 134 participants whose BMI were determined. Percentage body fat mass (%BF) and percentage visceral fat (%VF) were obtained by BIA using a hand-to-hand Omron body composition monitor with a weighing scale. Findings: Based on the WHO BMI criteria, 6.0 per cent of the participants were obese. However, according to BIA 18.7 and 20.9 per cent of the participants were obese according to % BF and %VF, respectively. The BMI and %BF showed higher prevalence of obesity among female participants (8.2 and 34.4 per cent, respectively) than male participants (4.1 and 5.5 per cent, respectively), whereas for %VF, obesity was higher among male participants than female participants (26.0 per cent, 14.8 per cent). There was significant positive correlation between BMI and % BF ( r = 0.604, p = 0.001); and between BMI and %VF ( r = 0.555, p = 0.001). Research limitations/implications: There are discrepancies in the prevalence of obesity in the study population as measured by BMI and BIA methods. This suggests that the BMI and BIA may not be reliable tools for assessing obesity in this population. Further studies are needed to determine the cut-offs for BMI and BIA that are associated with metabolic risk in the population. The small sample size limits the generalizability of findings of this study. Originality/value: Body composition tends to vary by ethnicity and race; hence, it is essential to determine the appropriate tool for assessing adiposity in African populations for prompt and targeted interventions.